2022
DOI: 10.3390/biom12081070
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 as a Promising Target in Aging and Aging-Related Diseases: A Promise or a Pledge

Abstract: The abnormal regulation and expression of microRNA (miRNA) are closely related to the aging process and the occurrence and development of aging-related diseases. Lethal-7 (let-7) was discovered in Caenorhabditis elegans (C. elegans) and plays an important role in development by regulating cell fate regulators. Accumulating evidence has shown that let-7 is elevated in aging tissues and participates in multiple pathways that regulate the aging process, including affecting tissue stem cell function, body metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 156 publications
(156 reference statements)
1
5
0
Order By: Relevance
“…Specifically, the down-regulated hsa-let-7 in iMSCs, which has been shown to exhibit crucial effects on MSCs regenerative properties, showed reduced expression after iPSCs reprogramming, and this reduction was also observed during iMSCs differentiation [ 79 , 80 ]. In concordance, previous studies have shown that hsa-let7b/i is elevated in aging tissues and participates in multiple pathways regulating the aging process, negatively affecting tissue stem cell function [ 81 ].…”
Section: Discussionsupporting
confidence: 81%
“…Specifically, the down-regulated hsa-let-7 in iMSCs, which has been shown to exhibit crucial effects on MSCs regenerative properties, showed reduced expression after iPSCs reprogramming, and this reduction was also observed during iMSCs differentiation [ 79 , 80 ]. In concordance, previous studies have shown that hsa-let7b/i is elevated in aging tissues and participates in multiple pathways regulating the aging process, negatively affecting tissue stem cell function [ 81 ].…”
Section: Discussionsupporting
confidence: 81%
“…The membrane structure of exosomes prevents the RNA contained in exosomes from being degraded, thus playing a more stable role. Let-7 miRNAs were the first discovered human miRNA with highly conserved sequence and function between species [ 30 ], and were revealed to be involved in different biological processes, including osteogenesis [ [31] , [32] , [33] , [34] ]. Related studies have found that Let-7 miRNAs were closely related to M2 macrophage polarization [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA replacement therapy is based on delivering exogenous miRNAs to patients to regulate abnormal functions [ 21 ]. For instance, let-7 is highly expressed in normal lung tissue and downregulated in lung cancer cells [ 23 ]. Let-7a inhibits NIRF expression in lung cancer while increasing p21 WAF1 expression and inhibiting cell proliferation [ 24 ].…”
Section: Mirna-based Lung Cancer Therapiesmentioning
confidence: 99%